Design keyed Hash function based on couple chaotic system - WEI Peng-cheng1; ZHANG Wei 1; 2; LIAO Xiao-feng 1 (Tongxin xuebao)
Analyzed the chaotic and cryptographic properties of a piecewise nonlinear map, a couple chaotic digital sys-tem was proposed based on perturbing which used the piecewise nonlinear, then a new approach to construct keyed Hash function was presented. The approach used the initial value of the couple chaotic system as the secret key and the coarse-graining trajectory as Hash values. Simulation results show that the chaotic keyed Hash function based on the couple chaotic system has good one-way, weak collision property, better security and it can be realized easily.